A corporate approach to enhancing lithium-ion battery safety through flame-retardant electrolyte development - Lee, Beomsu; Jung, Cheolsoo (Frontiers in Energy Research, 2025)
Lithium-ion batteries (LIBs) are integral to modern technology, yet their reliance on flammable liquid electrolytes poses significant safety challenges, especially in electric vehicles and large-scale energy storage systems. This paper presents the development of flame-retardant electrolytes utilizing the Define-Measure-Analyze-Design-Optimize-Verify (DMADOV) methodology to enhance both safety and performance of LIBs. The study initiates by defining the correlation between the properties of organic solvents and electrochemical stability, focusing on the overcharging risks that can induce thermal runaway. Through systematic measurement and analysis of candidate components, critical factors influencing the quality of flame-retardant electrolytes are identified. The design phase prioritizes the establishment of solid electrolyte interface (SEI) conditions for γ-butyrolactone (γ-BL), ensuring the electrolyte’s performance and stability in LIBs. The optimization phase further refines the SEI formation conditions to address performance challenges identified during initial design, incorporating related manufacturing processes. The final verification phase confirms the alignment of the flame-retardant electrolyte composition with optimized SEI conditions, establishing a viable electrolyte range for practical applications. The study demonstrates that the use of γ-BL markedly reduces the explosion risk due to overcharging. The final verification phase confirms the alignment of the flame-retardant electrolyte composition with optimized SEI conditions, establishing a viable electrolyte range for practical applications. Significantly, this study emphasizes the importance of robust SEI design in developing flame-retardant electrolytes with high-flash-point organic solvents like γ-BL, supported by validation experiments on patented technology. These advancements not only enhance the safety profile of LIBs but also demonstrate the potential for improved battery performance, paving the way for broader applications in energy storage solutions.